Internet-based infrastructures and online architectural education on design studios: perceived instructional strategies and students engagement - Baigi, Fatemeh; Yeganeh, Mansour; Bemanian, Mohammadreza (Frontiers in Built Environment, 2024)
The current study investigated the impact of perceived instructional strategies in online design studios on student engagement as a multidimensional construct. Given the rapid shift to online learning during the COVID-19 pandemic, understanding effective teaching strategies and their impacts on student engagement is crucial for enhancing overall student outcomes. The study also examined the role of learning motivation as a mediator in these relationships. A mixed-methods approach was employed, measuring a second-order construct of student engagement based on three reflective dimensions: cognitive, affective, and behavioral. Qualitative interviews with instructors revealed three main instructional strategies utilized in online design studios: learning by doing, learning with interaction, and learning from feedback. The present study analyzed self-report survey responses from 230 undergraduate architecture students across four major universities in Iran, utilizing partial least squares structural equation modeling (PLS-SEM). Based on the results, the perceived learning by doing (PLD) and learning with interaction (PLI) significantly improve student engagement. In contrast, the perceived learning from feedback (PLF) fails to influence student engagement directly. Additionally, intrinsic and extrinsic motivation mediated the impact of PLI and PLF on student engagement. These findings highlight the importance of effective instructional strategies in online design studios. Additionally, the results provide valuable insights for future pedagogical practices in online education, offering guidance for instructors aiming to enhance student outcomes in this dynamic learning environment.